AN ANALYSIS OF TRANSITIVITY IN READING TEXT FOR SECOND GRADE STUDENTS’ OF SENIOR HIGH SCHOOL - Annisa Nurhadi Maya; Eliza; Loli Safitri (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
Abstract: This research concerned transitivity in reading text for senior high school. The purposes of this research were to describe and to find out the dominant process types of transitivity occurred in the reading text. This research was descriptive qualitative. The data was obtained from reading text in English textbook entitled Pathway to English. The result of the research were six types of process that occurred in the textbook. There were material process (38%), relational process (30%), verbal process (20%), mental process (19%), behavioural process (4%), and existential process (2%). The dominant types of transitivity was material process. It means that reading passage in English textbook entitled Pathway to English contained action and physicaly. Futhermore, the benefit that can be gained from analyzing the transitivity in the text could stimulate the reading skills to comprehend the idea and information in a text that could be applied in spoken and written texts.